mSphere of Influence: Trypanosoma cruzi genome in 3D action - Luisa Berná (mSphere)
ABSTRACT Luisa Berná works in the field of comparative and evolutionary genomics in unicellular eukaryotes. In this mSphere of Influence article, she reflects on how advances in three-dimensional genome organization have reshaped our understanding of parasite biology. She discusses how recent findings uncover the distinctiveness of the three-dimensional architecture of Trypanosoma cruzi’s genome and its functional implications. Berná argues that integrating structural genomics into parasite research is essential for advancing our understanding of genome organization and its role in shaping parasite biology, particularly in the context of neglected tropical diseases.